2022
DOI: 10.1186/s12912-022-00921-2
|View full text |Cite
|
Sign up to set email alerts
|

Caring ability of nursing students pre- and post-internship: a longitudinal study

Abstract: Background Nursing students’ internship experiences may significantly impact their caring ability. However, there is a lack of comprehensive evaluation of undergraduate nursing students' caring ability pre-and post-internship in China. This study aimed to explore the differences in the caring ability of undergraduate nursing students before and after internship. Methods The sample comprised 305 undergraduate nursing students who had undergone inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
4
10
1
Order By: Relevance
“…This demonstrates that narrative pedagogy is more effective than traditional teaching methods in cultivating nursing students’ care ability. In keeping with findings of Hu et al [ 6 ], cognitive scores were highest among the three CAI dimensions, followed by patience and courage. This may be the result of nursing being a profession dominated by women.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This demonstrates that narrative pedagogy is more effective than traditional teaching methods in cultivating nursing students’ care ability. In keeping with findings of Hu et al [ 6 ], cognitive scores were highest among the three CAI dimensions, followed by patience and courage. This may be the result of nursing being a profession dominated by women.…”
Section: Discussionsupporting
confidence: 90%
“…This quasi-experimental study explored narrative teaching as a strategy to develop nursing students’ humanistic care ability for hospitalized children. Our findings showed that nursing students had low humanistic caring ability, which is in line with findings from a longitudinal study on the caring ability of Chinese nursing students pre- and post-internship [ 6 ]. In China, nursing undergraduate education placed a greater emphasis on developing nursing students’ professional knowledge and practical skills.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The “knowledge” subscale shows the degree of perception of oneself and the person who is under the nurse’s care; “courage” can be seen as the ability to cope with sudden and unknown situations in the care process; and “patience” is related to acceptance and perseverance in professional practice [ 1 ]. Similar results were obtained by researchers from China [ 30 ], where the vast majority of respondents were women who displayed greater patience than courage in patient care, as this depends on how much professional experience has been gained [ 30 , 34 ].…”
Section: Discussionsupporting
confidence: 82%
“…The overall score of the CAI indicates that students present with low caring abilities. Similar results were obtained for undergraduate students from China [ 30 , 31 ], and slightly higher scores were obtained for students from America [ 31 ]. Professional values and caring abilities may therefore depend on the geographical region in which nursing students receive education.…”
Section: Discussionsupporting
confidence: 81%